Air Temperature Characteristics, Distribution, and Impact on Modeled Ablation for the South Patagonia Icefield. Issue 2 (30th January 2019) - Bravo, C.; Quincey, D. J.; Ross, A. N.; Rivera, A.; Brock, B.; Miles, E.; Silva, A.
Abstract: The glaciers of Patagonia are the largest in South America and are shrinking rapidly, raising concerns about their contribution to sea level rise in the face of ongoing climatic change. However, modeling studies forecasting future glacier recession are limited by the scarcity of measured on‐glacier air temperatures and thus tend to use spatially and temporally constant lapse rates. This study presents 9 months of air temperature observations. The network consists of five automatic weather stations and three on‐glacier air temperature sensors installed on the South Patagonia Icefield along a transect at 48°45′S. Observed lapse rates are, overall, steeper on the east (−0.0072 °C/m) compared to the west (−0.0055 °C/m) and vary between the lower section (tongue, ablation zone) and the upper section (plateau, accumulation zone) of the glaciers. Warmer off‐glacier temperatures are found in the east compared to the west for similar elevations. However, on‐glacier observations suggest that the glacier cooling effect is higher in the east compared to the west. Through application of distributed temperature‐index and point‐scale energy balance models we show that modeled ablation rates vary by up to 60%, depending on the air temperature extrapolation method applied, and that melt is overestimated and sublimation is underestimated if the glacier cooling effect is not included in the distributed air temperature data. These results can improve current and future modeling efforts of the energy and mass balance of the whole South Patagonia Icefield. Key Points: Distinct lapse rates prevail on the east and west sides of the icefield A strong glacier cooling effect relative to off‐glacier air temperature was observed Ablation is estimated using temperature extrapolation approaches; divergent results highlight the need for realistic temperature distributions